Work-Life Balance and Wellbeing: The Moderating Role of Social Support - Alisa, Cici; Syahrizal, Syahrizal (Human Resource Management Studies, 2023)
This study analyzes (1) the effect of work life balance on well-being in the nurses at Ibnu Sina Hospital Simpang Empat Pasaman Barat (2) the effect of social support on well-being of nurses at Ibnu Sina Hospital, Simpang Empat, Pasaman Barat (3) the effect of work life balance on well-being in the nurses of the Ibnu Sina Hospital Simpang Empat Pasaman Barat with social support as moderation. This research is a causal research. The population in this study were nurses at the Ibnu Sina Hospital, Simpang Empat, Pasaman Barat. The number of samples used is the population of 80 people who are taken using saturated sampling. Collecting data using a questionnaire with a Likert scale. The analysis technique used is SEM using Smart PLS analysis. The results of this study show: (1) work life balance has a positive and significant effect on the welfare of nurses at the Ibnu Sina Simpang Empat Hospital in West Pasaman (2) Social support has a positive and significant effect on well-being for nurses at the Ibnu Sina Hospital, Simpang Empat, Pasaman Barat (3) social support does not significantly moderate the effect of work life balance on well-being in nurses at the Ibnu Sina Hospital, Simpang Empat, Pasaman Barat.